2021
DOI: 10.1371/journal.pone.0259695
|View full text |Cite|
|
Sign up to set email alerts
|

Potential of Landsat 8 OLI for mapping and monitoring of soil salinity in an arid region: A case study in Dushak, Turkmenistan

Abstract: Soil salinity is the most common land degradation agent that impairs soil functions, ecosystem services and negatively affects agricultural production in arid and semi-arid regions of the world. Therefore, reliable methods are needed to estimate spatial distribution of soil salinity for the management, remediation, monitoring and utilization of saline soils. This study investigated the potential of Landsat 8 OLI satellite data and vegetation, soil salinity and moisture indices in estimating surface salinity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Spatial resolution of satellite images is an important factor in determining and mapping salinity [ 14 , 20 , 56 ]. Therefore, Ahmed and Andrianasolo [ 57 ] revealed that soil salinity can be mapped in more detailed using SPOT XS images compared to Landsat TM images.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Spatial resolution of satellite images is an important factor in determining and mapping salinity [ 14 , 20 , 56 ]. Therefore, Ahmed and Andrianasolo [ 57 ] revealed that soil salinity can be mapped in more detailed using SPOT XS images compared to Landsat TM images.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, determining and monitoring soil salinity with classical methods (laboratory analysis) is costly and time-consuming. Unlike conventional methods, remote sensing technologies offer significant cost-effective advantages in determining soil salinity for large areas at high accuracy [ 5 , 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The availability of remote sensing data (RS) opens up new opportunities for assessing the state and monitoring of biotopes, including the saline ones. In particular, they are used to map saline biotopes [3,4], vegetation status [5,6], analysis of their spatiotemporal changes [7,8]. The state assessment of the biotopes allows to identify some factors that affect the distribution of birds that inhabit them.…”
Section: Introductionmentioning
confidence: 99%